FROM KNOWLEDGE MANAGEMENT THEORIES TO PRACTICE IN PUBLIC ORGANISATIONS: TOWARDS A TRANSDISCIPLINARY APPROACH (THEORETICAL BACKGROUND) - Davidova, Jelena; Kokina, Irena; Zarina, Zane (European Scientific Journal, ESJ, 2014)
Scientists and practitioners have developed and continue to refine methodologies of knowledge management with the aim to implement it into practice of public organisations. In recent studies, there has been an emphasis on the development of what can be considered a transdisciplinary approach in knowledge production and usage, where knowledge management, its theories, principles and practices are advanced. The aim of this study is to review the conceptual foundations of knowledge and knowledge management by advancing the conception of knowledge management in the context of transdisciplinary approach. The authors give an overview of the forms, levels and categories of knowledge. The increasing emphasis placed on knowledge in an organisational context has given rise to a new manifestation of capital which occurs as human or structural intellectual capital. By analysing theories on the essence of knowledge management, the viewpoint formed that knowledge management within an organisation should be viewed through the transdisciplinary approach, namely, production of knowledge that rises above disciplines should be done by collaboration of both academic and nonacademic representatives, who offer a new compass and map for complex problem solving.